Role of CD38 in mediating the effect of Bacillus on acute pancreatitis: a study of mediated Mendelian randomization - Xiao, Junhao; Tao, Zhuoyan; Luo, Mingjian; Yan, Yong; Ke, Shaobiao; Mao, Benliang; Zhan, Jiulin; Wang, Zhe; Wang, Bailin; Li, Zhiwei (Frontiers in Immunology, 2024)
BackgroundSome studies suggest a potential link between intestinal flora and acute pancreatitis (AP). However, the causal relationships between specific intestinal flora and AP, and the possible mediating role of immune cell traits, remain unclear.MethodsA genome-wide association study (GWAS) involving 5,959 participants was conducted to identify genetic instrumental variables associated with 473 intestinal flora taxa. Summary statistics for AP were obtained from the UK Biobank. Immune cell traits were also identified using large-scale GWAS summary data. We employed a two-sample bidirectional Mendelian randomization (MR) approach to investigate the causal relationships between intestinal flora, immune cell traits, and AP, with inverse variance weighting (IVW) as the primary statistical method. Sensitivity analyses, including the MR-Egger intercept test, Cochran’s Q test, MR-PRESSO test, and leave-one-out test, were conducted to assess the robustness of our findings. Additionally, we explored whether immune cell traits mediate the pathway from intestinal flora to AP.Results11 positive and 11 negative causal relationships were identified between genetic susceptibility in intestinal flora and AP. Furthermore, 19 positive and 9 negative causal relationships were observed between immune cell traits and AP. Notably, CD38 mediated the causal relationship between Bacillus C and AP.ConclusionsThis study is the first to uncover novel causal relationships between various intestinal flora and acute pancreatitis, emphasizing the mediating role of immune cell traits in the pathway from intestinal flora to AP. It also provides new evidence supporting the conditional pathogenicity of the Bacillus genus.